Psychological effects of People Affected by Leprosy (PAL) and social reintegration strategies - Priyanto, Priyanto; Yulianigsih, Nengsih (Poltekkes Kemenkes Bandung, 2026)
Background: Leprosy is a chronic infectious disease that has an impact not only on the physical but also psychosocial aspects of its survivors. Even though they have been declared medically cured, people affected by leprosy still face stigma and discrimination that hinder social reintegration. This is reflected in the high number of leprosy cases in Indramayu Regency, which reached 3,777 cases in. Objective: This study aimed to analyze the psychological effects experienced by People Affected by Leprosy (PAL) and its relationship with the social reintegration process in Indramayu Regency. Methods: The research used a quantitative design with a descriptive-analytical survey approach. The sample was determined through purposive sampling technique with a total of 208 PAL respondents who had been declared medically cured and had post-treatment social interaction experience. Data collection was carried out using online and offline questionnaires with the assistance of field cadres and health workers. Data analysis includes descriptive statistics, Chi-Square tests, and Spearman correlation. Results: The results showed that the majority of respondents experienced significant psychological impacts, including shame (90.9%), low self-esteem (95.4%), loss of zest for life (77.3%), fear of social rejection (68.2%), and experiences of discrimination (72.8%). Bivariate analysis showed that shyness, low self-esteem, fear of rejection, and experiences of discrimination were significantly associated with social reintegration (p<0.05), while family support and community acceptance were positively associated with the reintegration process. Conclusion: This research confirms that PAL social reintegration requires community-based multidimensional interventions, strengthening family support, and sustainable public education to reduce stigma and discrimination.